Making Rocky Mountain National Park : Making Rocky Mountain National Park - Frank, Jerry J. (Book collections on Project MUSE., 2013)
"On September 4, 1915, hundreds of people gathered in Estes Park, Colorado, to celebrate the creation of Rocky Mountain National Park. This new nature preserve held the promise of peace, solitude, and rapture that many city dwellers craved. As Jerry Frank demonstrates, however, the park is much more than a lovely place. Rocky Mountain National Park was a keystone in broader efforts to create the National Park Service, and its history tells us a great deal about Colorado, tourism, and ecology in the American West. To Frank, the tensions between tourism and ecology have played out across a natural stage that is anything but passive. At nearly every turn the National Park Service found itself face-to-face with an environment that was difficult to anticipate--and impossible to control. Frank first takes readers back to the late nineteenth century, when Colorado boosters--already touting the Rocky Mountains' restorative power for lung patients--set out to attract more tourists and generate revenue for the state. He then describes how an ecological perspective came to Rocky in fits and starts, offering a new way of imagining the park that did not sit comfortably with an entrenched management paradigm devoted to visitor recreation and comfort. Frank examines a wide range of popular activities including driving, hiking, skiing, fishing, and wildlife viewing to consider how they have impacted the park's flora and fauna, often leaving widespread transformation in their wake. He subjects the decisions of park officials to close but evenhanded scrutiny, showing how in their zeal to return the park to what they understood as its natural state, they have tinkered with its features--sometimes with less than desirable results. Today's Rocky Mountain National Park serves both competing visions, maintaining accessible roads and vistas for the convenience of tourists while guarding its backcountry to preserve ecological values. As the park prepares to celebrate its centennial, Frank's book advances our understanding of its past while also providing an important touchstone for addressing its problems in the present and future"--